(untitled) (International Current Pharmaceutical Journal, 2012)
Floating matrix tablets of losartan potassium were developed with an aim to prolong its gastric residence time and increase the bioavailability of drug. Rapid gastrointestinal transit could result in incomplete drug release from the drug delivery system above the absorption zone leading to diminished efficacy of the administered dose. The tablets were prepared by wet granulation technique, using polymers Methocel K15 and Methocel K100 in combination with other standard excipients. Sodium bicarbonate was incorporated as gas generating agent. The effects of sodium bicarbonate and polymers on drug release profile and floating properties were investigated. It was found that viscosity of Methocel K15 and Methocel K100 along with sodium bicarbonate had significant impact on the release and floating properties of the delivery system. The decrease in the release rate was observed with an increase in the viscosity of the polymeric system. Polymer with high viscosity Methocel K100 was shown to be beneficial than low viscosity polymer Methocel K15 in improving the floating properties of gastric floating drug delivery system (GFDDS). The observed difference in the drug release and floating properties of GFDDS could be attributed to the difference in the basic properties of two polymers, Methocel K15 and Methocel K100 due to their water uptake potential and functional group substitution. The release mechanism were explored and described with zero-order, first-order and Korsmeyer-Peppas equations. The drug release profiles and buoyancy of the floating tablets were stable when stored at 40°C/75% RH for 6 months. DOI: http://dx.doi.org/10.3329/icpj.v2i1.12872 International Current Pharmaceutical Journal 2012, 2(1): 11-17